Komitmen Organisasi dan Sikap Whistle-Blowing: Apakah Hubungannya Dimoderasi Oleh Persepsi Dukungan Organisasi? - M Sandi Marta; Anis Eliyana (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2019)
The explanation of how individuals do whistle-blowing is actually influenced by interpersonal factors of employees. This article aims to develop an original framework that explains the role of moderating perception of organizational support between organizational commitment and whistle-blowing attitudes. This research is an empirical study at state universities in the city of Bandung with multivariate analysis as a tool in explaining the research hypothesis. The results show that organizational commitment empirically has a positive effect on whistle-blowing attitudes. Furthermore, the perceived organizational support positively moderates the influence between organizational commitment and whistle-blowing attitudes.